2020
DOI: 10.3390/ijms21051625
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Redox Signaling of the Nucleoredoxin-Like-1 Gene for the Treatment of Genetic Retinal Diseases

Abstract: The loss of cone photoreceptor function in retinitis pigmentosa (RP) severely impacts the central and daily vision and quality of life of patients affected by this disease. The loss of cones follows the degeneration of rods, in a manner independent of the causing mutations in numerous genes associated with RP. We have explored this phenomenon and proposed that the loss of rods triggers a reduction in the expression of rod-derived cone viability factor (RdCVF) encoded by the nucleoredoxin-like 1 (NXNL1) gene wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 178 publications
0
19
0
Order By: Relevance
“…Most forms of RP are due to primary damage of rod cells, which is followed by a secondary loss of cones ( Figure 1C; Sancho-Pelluz et al, 2008). RdCVF is a retina-specific trophic factor that induces cone survival and functional rescue in RP animal models (Leveillard et al, 2004;Yang et al, 2009) by modulating energy metabolism, accelerating glucose entry and enhancing aerobic glycolysis, thus holding good promises as an effective AAV-mediated mutation-independent therapy (Leveillard and Sahel, 2010;Ait-Ali et al, 2015;Byrne et al, 2015;Clerin et al, 2020).…”
Section: Neuroprotection Approachesmentioning
confidence: 99%
“…Most forms of RP are due to primary damage of rod cells, which is followed by a secondary loss of cones ( Figure 1C; Sancho-Pelluz et al, 2008). RdCVF is a retina-specific trophic factor that induces cone survival and functional rescue in RP animal models (Leveillard et al, 2004;Yang et al, 2009) by modulating energy metabolism, accelerating glucose entry and enhancing aerobic glycolysis, thus holding good promises as an effective AAV-mediated mutation-independent therapy (Leveillard and Sahel, 2010;Ait-Ali et al, 2015;Byrne et al, 2015;Clerin et al, 2020).…”
Section: Neuroprotection Approachesmentioning
confidence: 99%
“…Viral-mediated expression of RdCVF into mouse models of retinal degeneration showed promising results (Y. Yang et al, 2009;Byrne et al, 2015) with subsequent development of a vector for near future clinical trials (Clerin, Marussig, Sahel, & Leveillard, 2020) (Table 3).…”
Section: Neuroprotective Therapiesmentioning
confidence: 99%
“…RdCVF is believed to stimulate glucose transport via GLUT1 into cone photoreceptors which in turn stimulates aerobic glycolysis and cone survival (Ait‐Ali et al, 2015). Viral‐mediated expression of RdCVF into mouse models of retinal degeneration showed promising results (Y. Yang et al, 2009; Byrne et al, 2015) with subsequent development of a vector for near future clinical trials (Clerin, Marussig, Sahel, & Leveillard, 2020) (Table 3).…”
Section: The Future Of Ocular Gene Therapy: Tackling New Genes With Nmentioning
confidence: 99%
“…In the early stage of RP, the loss of rods triggers a reduction in the expression of rod-derived cone viability factor (RdCVF), encoded by the nucleoredoxin-like 1 (NXNL1) gene, which interrupts the metabolic and redox signaling between rods and cones 15 . The administration of a recombinant AAV encoding the two products of the NXNL1 gene, the trophic factor RdCVF and the thioredoxin enzyme RdCVFL, could theoretically prevent cone vision loss in all genetic forms of RP 16 . We have shown that the NXNL1 gene product, RdCVFL, is expressed in chicken cone-enriched cultures 17 and where it plays a protective role 18 .…”
Section: Introductionmentioning
confidence: 99%